Postnephrectomy renal arteriovenous fistula - Kocakoc, E; Poyraz, AK; Cetinkaya, Z; Bozgeyik, Z (Amer Inst Ultrasound Medicine, 2004)
Renal arteriovenous malformations (AVMs) are abnormal communications between the renal arterial and venous systems. Renal AVMs are uncommon, and in large autopsy series, their estimated rate is less than I case per 30,000 patients. This incidence ranges from 1 case per 1000 to 2500 patients in clinical studies, which include patients who underwent interventional techniques.' Acquired arteriovenous fistulas (AVFs) are the most common type and constitute 70% to 80% of renal AVMS.(2) Congenital and idiopathic AVFs constitute less than 30% of these malformations.(3) A postnephrectomy renal AVF with an aneurysmal lesion is a rare clinical entity that may cause high-output heart failure.(4) We present a case of a postnephrectomy renal AVF after a gunshot injury.
Keywords: Diagnosis; Aneurysm; Artery